A descriptive study on the influence of print advertising elements on selected consumers of clothing - Viron, Charles B. (UP College of Home Economics, 2012)
This is a descriptive study that aimed to determine how print advertisements influence selected young professionals' reception, and perception. Specifically, the study identified the elements in print advertising that contributed in consumer reception and perception of clothing brands, determined the effectiveness of print advertising and its elements in influencing the brand choice or preference of consumers of clothing brands, determined motivations of consumers in selecting a particular clothing brand, and determine the relationship of respondents' demographics and print advertisements' influence on the reception, perception and preference over clothing brands. The research used the survey method that was conduced among purposely selected 47 young professionals working in the US Mortgage Collections Department of Citigroup Business Process Solutions Pte. Ltd. Data analysis was done through the use of non-parametric statistical tests and simple tabulation and graphical representation of the data. Findings show that the respondents' reception, perception and preference for clothing brands are influenced by the elements of print ads like artwork, photos, and concepts. This is indicated by the level of agreement expressed by the respondents. Although personal of purchasing differ between genders, there was no relationship between gender, civil status and income and the responses of the respondents, In general, print advertisement influence perception and preference through its ability to grab its audience attention and holding until the message has been articulated to the audience.